PERSEPSI MASYARAKAT TENTANG PEMBANGUNAN JALAN LINGKAR LUAR KOTA PALU (JLLKP) DI KELURAHAN LAYANA KOTA PALU - Wolor, Mery Pricelia (Katalogis, 2015)
This study aims to determine the public perception of the construction of Palu Outer City Ring Road in Layana Village in Palu City. Firstly, this research found that the number of businesses are considered less impact. This means that the construction of Palu outer city ring road has less impact on the number of business. Secondly, the price of the buildings through the construction of Palu outer city ring road has been increased. It means that the project has significant impact on the price of buildings. Thirdly, the respondents claim that there are significant impact of the construction of Palu outer city ring road on their purchasing and selling of products. Fourthly, it can also be seen that this contruction has contributed to support their promotion of their business. The construction of Palu outer city ring road has positive impact to increase the number of their customers. Fifthly, the project has contributed to support their products distribution. The time travel can be shorten by the construction of Palu outer city ring road so that they can easy to travel into other areas as well as strengthening the relationship with other region. Lastly, this the construction of Palu outer city ring road may also given a change to save more money because of low costin local transport